Urgensi Fiqih (Adab Guru dan Murid) dalam Membentuk Karakter Peserta Didik di Era Globalisasi: Penelitian - Ulinnuha Yuana Putra; Azkia Faiqotun Ni’mah; Mohammad Sobirin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Education in the era of globalization is not only challenged by academic demands but also by an alarming crisis of character. Issues such as the decline of politeness, the erosion of respect for teachers, and the weakening of ethical conduct in the learning process have become fundamental concerns that require serious attention. In this context, fiqh al-adab—which encompasses ethical guidelines governing the teacher-student relationship in Islamic educational tradition—offers a relevant and transformative solution. This study employs a library research method by examining classical works of scholars such as Imam Nawawi, Al-Ghazali, and Al-Zarnuji, and exploring their contributions to character development in students. The findings reveal that teachers’ adab, such as sincerity, patience, humility, and professionalism in teaching, significantly influence the creation of a respectful and effective learning environment. Meanwhile, students’ adab toward teachers and knowledge—such as humility, focus during learning, proper etiquette in the classroom, and sensitivity to the teacher’s condition—contributes to shaping learners who are not only knowledgeable but also morally upright. Therefore, fiqh al-adab serves as a normative foundation for revitalizing character education amidst the moral challenges facing today’s younger generation.